Sexual Politics of Desire and Belonging. - Rumens, Nick (At the Interface/Probing the Boundaries, 36., 2007)
Designed for students, academics and the general reader alike, Sexual Politics of Desire and Belonging provides theoretical and empirical insights into the linkages between sexualities and forms of desire, and ways of belonging and relating to others in specific contexts and moments in time. Opening with a substantial introduction by one of the editors, this collection of thirteen essays is organised into three parts, each section making important contributions to contemporary debates regarding the sexual politics of citizenship, marriage, friendship, pornography, intimacies, eroticism and des.